The climax of prophecy : studies on the book of Revelation - Bauckham, Richard (T & T Clark, 1993)
The Apocalypse of John is a work of immense importance and learning. Yet among the major works of early Christianity included in the New Testament it has received relatively little scholarly attention. This work is a significant contribution to remedying this neglect. The author examines the meticulous literary artistry, creative imagination, radical political critique and profound theology of the Apocalypse of John. It is a sustained enterprise to understand both the form and the message of the Apocalypse in its literary and historical contexts. An invaluable and illuminating work for students.